Disseminated Emergomycosis in a Person with HIV Infection, Uganda - Rooms, Isabelle; Mugisha, Peter; Gambichler, Thilo; Hadaschik, Eva; Esser, Stefan; Rath, Peter-Michael; Haase, Gerhard; Wilmes, Dunja; McCormick-Smith, Ilka; Rickerts, Volker (Emerging Infectious Diseases., 2019)
We describe emergomycosis in a patient in Uganda with HIV infection. We tested a formalin-fixed, paraffin-embed¬ded skin biopsy to identify Emergomyces pasteurianus or a closely related pathogen by sequencing broad-range fun¬gal PCR amplicons. Results suggest that emergomycosis is more widespread and genetically diverse than previously documented. PCR on tissue blocks may help clarify emer¬gomycosis epidemiology.
Keywords: Disseminated; Emergomycosis; A person; HIV; Infection